Notes on Peruvian Ribes cuneifolium and Ribes ovalifolium (Grossulariaceae) - Maximilian, Weigend (2022)
The genus Ribes (Grossulariaceae) is widespread across the northern hemisphere, but also species-rich in the tropical Andes. In the Peruvian Andes the genus is mostly found in at least seasonally moist cloud and scrub forests, subparamo habitats and hedges. However, some taxa are from more extreme habitats in semi-arid habitats of the western slope of the Andes (Andean scrub, Ribes ovalifolium) respectively high Andean puna and paramo habitats at elevations of up to 5100 m asl (Ribes cuneifolium and some doubtful segregates). These species share small, weakly divided leaves, making them quite atypical for the genus, usually with large, deeply three- to five-lobed leaves. Both the geographical ranges and the species delimitation for both taxa are poorly understood. We here propose the recognition of only two, well-differentiated species. Ribes ovalifolium can be shown to be wide-ranging from northern Ancash to Tacna, covering nearly the entire western flank of the Peruvian Andes. Similarly, Ribes cuneifolium can be shown to represent a single, wide-ranging species from high elevations of San Martín/La Libertad to Cuzco. There is considerable diversity on details of indument, flower color and leaf shape, but no clear dividing lines permitting the recognition of segregates such as Ribes incertum J.F.Macbr. The only exception are cloud-forest populations of Ribes cuneifolium in Pasco, which we propose to segregate as a new subspecies Ribes cuneifolium subsp. pascoense based on their considerably larger leaves and inflorescences.